Community-Based Tourism Impression Self-Esteem in Rural Tourism Development - Grace Amin; Filda Rahmiati; Yunita Ismail; Tasya Zahwa Prayoga (AIBPM Publisher, 2023)
Due to its distinctive nature, culture, and warm hospitality of the indigenous people, Indonesia is well renowned as a tourist destination. Both domestic and international tourists frequently visit a variety of tourist destinations. While some of the attractions are run by locals, others are overseen by outside organizations or foreign nationals. This study aims to analyze the role of indigenous peoples as their participation the development of tourism in Tanjung Lesung, Banten. To gather qualitative information, participant observation and in-depth interviews were performed. This study revealed that indigenous people may create a feeling of self-worth through communal development. Locals are willing to contribute their resources to the growth of tourism in their area. Increased local community self-esteem may have an impact on the competitiveness of rural tourism.